PENGARUH KEBIJAKAN KESEHATAN TERHADAP PERLINDUNGAN HUKUM BAGI TENAGA MEDIS DAN PASIEN - Widjaja, Gunawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The influence of health policies on legal protection for medical personnel and patients is an important issue in efforts to improve the quality of health services. Clear and comprehensive policies are needed to regulate the rights and obligations of medical personnel and patients, as well as to reduce the risk of legal disputes. With good regulations, medical personnel can carry out their duties professionally and patients are protected from malpractice or medical negligence. In addition, specific policies regarding medical procedures, drug management, and health service standards provide clear guidance for medical personnel, thereby minimizing the potential for legal violations. Health policies must also ensure equitable access to health services for all levels of society, including vulnerable groups. Thus, effective health policies can guarantee adequate legal protection for medical personnel and patients and increase public trust in the health system.